55.2k views
0 votes
How to solve this equation: ax² - 5x + 2 = 0

User Farhan C K
by
4.8k points

1 Answer

1 vote

Answer:


x=\frac{5(+/-)√(25-8a)} {2a}

Step-by-step explanation:

we know that

The formula to solve a quadratic equation of the form


ax^(2) +bx+c=0

is equal to


x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}

in this problem we have


ax^(2) -5x+2=0

so


a=a\\b=-5\\c=2

substitute in the formula


x=\frac{5(+/-)\sqrt{-5^(2)-4(a)(2)}}{2a}


x=\frac{5(+/-)√(25-8a)} {2a}

User Stephen Petschulat
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.